2015
DOI: 10.1002/ptr.5418
|View full text |Cite
|
Sign up to set email alerts
|

3,6-Dimethoxy-6″,6″-Dimethyl-(7,8,2″,3″)-Chromeneflavone, a Flavonoid Isolated fromLonchocarpus AraripensisBenth. (Fabaceae), Reduces Nociceptive Behaviour in Mice

Abstract: Lonchocarpus araripensis Benth. is largely distributed in the northeast region of Brazil. It is popularly known as 'sucupira'. Recent studies have shown that some species of Lonchocarpus have interesting pharmacological activities. In this study, we evaluated the antinociceptive effect of a flavone isolated from L. araripensis. The chemical examination resulted in the isolation of 3,6-dimethoxy-6″,6″-dimethyl-(7,8,2″,3″)-chromeneflavone (DDF). The structure of the compound was established by spectral analysis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…Among the phenolic compounds belonging to the class of flavonoids, the phytochemical prospection of extracts revealed the presence of catechins, chalcones, aurones, flavones, flavonols, xanthones, flavonones, flavononols and leucoanthocyanidins (Table 3). Studies on the phytochemical prospection of plant extracts of D. araripensis showed the presence of flavonoid substances (chalcones, flavones and flavanones) from researches with different parts of the plant (Lima, 2007;Almeida et al, 2015), corroborating with the results found in this study.…”
Section: Phytochemical Analysissupporting
confidence: 90%
“…Among the phenolic compounds belonging to the class of flavonoids, the phytochemical prospection of extracts revealed the presence of catechins, chalcones, aurones, flavones, flavonols, xanthones, flavonones, flavononols and leucoanthocyanidins (Table 3). Studies on the phytochemical prospection of plant extracts of D. araripensis showed the presence of flavonoid substances (chalcones, flavones and flavanones) from researches with different parts of the plant (Lima, 2007;Almeida et al, 2015), corroborating with the results found in this study.…”
Section: Phytochemical Analysissupporting
confidence: 90%
“…Natural compounds have been used for different therapeutic applications, including antinociceptive (Almeida et al, 2015;Bonjardim et al, 2011;Franco et al, 2011;Melo et al, 2014), antioxidant (Paixão et al, 2013), and antiinflammatory (Veras et al, 2013;Paixão et al, 2015) activities. However, there are few studies that describe pharmacological effects of a nanostructured gel of thymol in acute periodontitis model.…”
Section: Introductionmentioning
confidence: 99%